(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
Indonesian’s consumption on milk has increased by year to year. Bear Brand is considered as one of qualified brands for its benefits. Compared to other brands, Bear Brand is continously increasing on its sales even it has the same quality and higher. The aim of this study is to analyze the influence of product quality, price, and brand image on purchasing decisions, and which the most dominant variable influencing on purchasing decisions. This research used quantitative research. The populations were consumers of Bear Brand in Yogyakarta. This research sample was determined by purposive sampling technique as many as 100 people. Data analysis used multiple regression analysis. The results showed that product quality and, price had an effect on the decision to buy Bear Brand in Yogyakarta, while brand image had no effect on the decision to buy Bear Brand milk in Yogyakarta. The result showed that the most dominant variable influencing on purchasing decisions is the price variable.